یوٹیوب سےکمائی اور تعاؤن علیٰ المعصیۃ کے پہلوں کا حنفی فتاویٰ کی روشنی میں تجزیاتی مطالعہ: An Analytical Study of Earning through YouTube and Its Aspects of Cooperation in Sin in the Light of Ḥanafī Fatāwā - Hamza Shoaib; Hafiz Abdul Basit Khan (Al Basirah, 2025)
In today’s digital age, there are numerous emerging avenues to earn money online, with YouTube standing out as one of the most popular and influential platforms. However, a critical concern frequently raised is whether monetizing YouTube content—particularly through advertisements—constitutes cooperation in sin (taʿāwun ʿala al-maʿṣiyah). It is the responsibility of contemporary scholars to examine this issue thoroughly and provide clear religious guidance. Monetization on YouTube has become one of the most debated and complex topics in modern Islamic finance and ethics. The already available literature discusses earning through YouTube, in social and economic perspectives, however in term of sharia ruling about that, various fatawas are issued to clarify the status of YouTube earning in the light of Islam. Although many scholars have already issued fatwas and guidelines regarding YouTube earnings, the dynamic and ever-evolving nature of the platform has led to a wide range of interpretations. Through qualitative research methodology, this paper has selected various Hanafi fatawas issued in Pakistan regarding YouTube earning. Moreover, recent updates to YouTube’s monetization policies and the introduction of new revenue streams have broadened the scope for further inquiry. This study aims to bridge the existing knowledge gap by critically reviewing earlier scholarly positions, identifying the most sound and balanced viewpoint, and analyzing new methods of earning on YouTube in light of Sharia principles. It concludes that earing through You Tube is allowed if the content is lawful in Islam otherwise not, but promoting immoral behavior through ads is not allowed. In conclusion, the income earned by a content creator through uploading videos and receiving increasing viewership can be deemed permissible when classified under the category of hiba (gift).